Arte e política no romantismo alemão - Gabriel Lago de Sousa Barroso (2014)
This thesis investigates the relation between art and politics on German Romanticisms thought and, more specifically, on the period known as First Romanticism (Frühromantik), taking as subject the work of two authors, Friedrich Schlegel e Novalis (Friedrich von Hardenberg). The art or the poetry, as the romantics call the principle of creation that determines any truly artistic activity, performs a fundamental role in the first romantic thought and allows the construction of a comprehension that faces the problem of the political. The research intends to interpret this relation, starting from the poetical-philosophical thought of the authors to develop, then, the consequences that follow on their political philosophy and their philosophy of the State. For that purpose, it is considered not only the perspectives that emerge from the idealist revolution and from the growing importance of art on that period, but also the historical horizon designed by the French Revolution, which creates a situation, at the same time, of crises and of disclosure of possibilities to a new project of social and political life. Therefore, standing from an aesthetics and hermeneutical imperative, Romanticism develops a solution to the political questions that arise at this decisive moment of Modernity, guided by the poetic principle. Inside the project of a new mythology, the romantics articulate a form of legitimation and integration of the community directed by the constitution of a poetical symbolism and a collective imaginary, that seeks to revert the diagnosis that presents the modern age as a moment of dissolution of common life into the boundaries of the private sphere, and also aims to provide, by the constant creative process, the rejuvenation of culture itself. The ideal of formation (Bildung), on its turn, is thought by the First Romanticism as a superior politics, which means, a path to integrate the different domains of culture that were, at first, found apart, as well as a means to conquer the plenitude of human existence. Formation turns out to be the supreme good and the objective of the State taken as a form of political organization. From this standpoint emerges the concept of poetic State that, conducted by the aesthetic imperative, organizes itself by the relationship between me and you, constituting a political life where each part is recognized as mediator of the whole. This concept is directly linked to the romantic criticism of the illuminist conception of the State as machine, which is guided by the mechanic metaphor and, as a result, treats the citizen according to a relation of cause and effect, deprived from the principle of freedom of thought. At last, the work intends to comprehend Romanticisms political project formulated by the integration between poetry and history. History is invoked here not only as a glance to the past, but also as a poetical vision of the future, that aims to the creative disclosure of possibilities in the midst of the tension with the present, framed as a political project of enlightening the humanity.